2018
DOI: 10.1002/smll.201704053
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Spectrum Selectivity for Multiphoton Absorption with Enhanced Visible Light Trapping in ZnO Nanorods

Abstract: Observation of visible light trapping in zinc oxide (ZnO) nanorods (NRs) correlated to the optical and photoelectrochemical properties is reported. In this study, ZnO NR diameter and c-axis length respond primarily at two different regions, UV and visible light, respectively. ZnO NR diameter exhibits UV absorption where large ZnO NR diameter area increases light absorption ability leading to high efficient electron-hole pair separation. On the other hand, ZnO NR c-axis length has a dominant effect in visible l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…79 In addition, antibacterial properties can be manipulated by different morphologies such as nanocombs, nanorods, nanobelts, nanowires, nanosheets, nanoflowers, and snowflakes, and such structures can be achieved by changing the preparation method. [80][81][82][83] Compared with spherical particles, rod-shaped particles are more likely to penetrate the cell membrane, and thus have stronger bactericidal properties. 84 Talebian et al 85 compared the same volumes of ZnO-NPs in flower, rod, and ball structures and showed that flower-shaped particles had the highest specific surface area with more Zn 2+ release and the strongest antibacterial properties.…”
Section: Antibacterial Properties Of Zno-nps Antibacterial Mechanism mentioning
confidence: 99%
“…79 In addition, antibacterial properties can be manipulated by different morphologies such as nanocombs, nanorods, nanobelts, nanowires, nanosheets, nanoflowers, and snowflakes, and such structures can be achieved by changing the preparation method. [80][81][82][83] Compared with spherical particles, rod-shaped particles are more likely to penetrate the cell membrane, and thus have stronger bactericidal properties. 84 Talebian et al 85 compared the same volumes of ZnO-NPs in flower, rod, and ball structures and showed that flower-shaped particles had the highest specific surface area with more Zn 2+ release and the strongest antibacterial properties.…”
Section: Antibacterial Properties Of Zno-nps Antibacterial Mechanism mentioning
confidence: 99%
“…15−20 The application of ZnO nanostructures has been significant in almost every scientific field, to name a few, antibacterial material, 21,22 environmental purification and photocatalyst activity applications, 23 water-splitting devices, 24 organic and inorganic photovoltaics solar cells, 25−27 ultraviolet (UV) photodetectors, 28 gas sensors, 29 thin-film transistors, 30 piezoelectric and dielectric devices, 31 light-emitting diodes, 32 and laser diodes. 33 Many nanostructures have been built in optoelectronics, 34 for instance, inhomogeneous nanoparticles, 15,35 nanowires, 16,17 nanorods, 18,19,36 and nanosheets. 20,37 Furthermore, the studies on ZnO point defects, 38 oxygen deficiency, 39 Zn vacancy, 40 and introduction of various dopants 41 have outlined the different abilities of ZnO by band gap engineering.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The choices of emitting materials in OLED's device fabrication could provide the desired light-emitting color as well as the device's efficiency and stability. 3 One of the approaches to improve OLED's performance is to synthesize new materials, which requires advanced chemical skills. Alternatively, researchers use commercially accessible OLED material polymers and combine them to form composites with inorganic substances, thereby modifying their PL characteristics.…”
Section: Introductionmentioning
confidence: 99%